Niall Ferguson's networld [videorecording (DVD)] - Ferguson, Niall; Ferguson, Niall (PBS, 2020)
In this groundbreaking new series hosted by Niall Ferguson and based on his bestselling book The Square and the Tower, Ferguson visits network theorists, social scientists, and data analysts to explore the history of social networks. Ferguson demonstrates how human behavior, disruptive technology, and the profit motive can energize ideas and communication, ultimately changing the world.